2016
DOI: 10.3201/eid2212.160017
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Characterization and Strain Comparison of VT2f-ProducingEscherichiacoliCausing Hemolytic Uremic Syndrome

Abstract: Strains from diarrheal illnesses could be transmitted from pigeons, but HUS-associated strains may derive from phage acquisition by isolates with larger virulence assets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…Accordingly, the phylogenetic and structural analyses showed the phage phi467, carrying the Stx2f-coding genes, falling into a clade separated from the others ( Figures 3 – 5 ). We did not include many Stx2f-encoding phages in this study as they are not available in the public databases for downloading, but previous evidences showed that these phages share a very high degree of similarity ( Grande et al, 2016 ). It is thus conceivable that they could have descended from a common ancestor and possibly remained confined to the pigeon host.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the phylogenetic and structural analyses showed the phage phi467, carrying the Stx2f-coding genes, falling into a clade separated from the others ( Figures 3 – 5 ). We did not include many Stx2f-encoding phages in this study as they are not available in the public databases for downloading, but previous evidences showed that these phages share a very high degree of similarity ( Grande et al, 2016 ). It is thus conceivable that they could have descended from a common ancestor and possibly remained confined to the pigeon host.…”
Section: Discussionmentioning
confidence: 99%
“…Subtypes Stx2a, Stx2c and Stx2d are associated with STEC infections in humans [11,15,16,17], while Stx2e, Stx2f, Stx2g are mainly found in animals [2,10,11]. Some studies have suggested that STEC strains producing Stx2f can cause diarrhoea in humans [18]; however, recently, STEC strains carrying the stx2f gene have been isolated from patients with hemolytic uremic syndrome (HUS) [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Striking phage-related variability in toxin production has been observed in clinical isolates of O157 as well as in other O groups (O83, O111, and O145). The genotype of the bacteriophage and host strain factors are relevant to STEC pathogenesis (158) as was recently demonstrated in a whole genome sequencing comparison of Stx2f-producing STEC strains, some of which were isolated from patients with HUS (63). In that study, only the three strains isolated from HUS patients had the EPECassociated efa1 gene, which resides on the PAI OI122, the STEC plasmid genes ehxA, espP, and katP, and intimin type n (xi) or b.…”
Section: Stx Types and Subtypesmentioning
confidence: 80%
“…Some studies suggested that an STEC strain that produce Stx2f can cause mild diarrhea or can be asymptomatic (54,126), but it appears to be rare (71,124). However, in a recent study an STEC O8:H19 strain that carried both stx 2f and eae was isolated from an HUS patient in The Netherlands (53), and others have also reported isolating Stx2f-producing STEC strains from HUS patients (63). Additional information is needed to understand the association between Stx2f and severe illness.…”
Section: Stx Types and Subtypesmentioning
confidence: 99%